Pembuatan Bot Telegram Untuk Layanan Pencarian Hadis Riwayat Sahih Bukhari - Gunawan Setia Wiguna; Nazruddin Safaat Harahap; Iwan Iskandar; Muhammad Affandes (Jurnal Informatika Terpadu, 2022)
Books about hadith are often found in bookstores and libraries. Although someone can access hadith via books, not all Indonesians have hadith books and are less interested in looking for hadith via book format. With the development of technology, bots or chatbots in the Telegram application provide information more easily. Hadith search using bot technology is required to make it easier for people the search about hadith. Telegram bot creation for hadith searches using data from Sahih Bukhari's book. The compiler of the Sahih Bukhari book group the hadiths according to specific topics into several books and chapters. The purpose of the make it easier to look at the hadith by the chapter. Telegram bot creation used the prototyping method and successfully created the bot as a hadith search service. Based on Black Box testing, the bot success ran all commands as expected. The User Acceptance Test (UAT) on the bot got a total result of 82,8%. The test results show that respondents' level of acceptance by the Telegram bot for hadith search includes the category strongly agree. From the results of the UAT test, it can conclude that users can accept and use the bot according to their needs.